Induction of dormancy by confinement: An agarose‐silica biomaterial for isolating and analyzing dormant cancer cells. Issue 12 (13th May 2021) - Preciado, Julian; Lam, Tiffany; Azarin, Samira M.; Lou, Emil; Aksan, Alptekin
Abstract: The principal cause of cancer deaths is the residual disease, which eventually results in metastases. Certain metastases are induced by disseminated dormancy‐capable single cancer cells that can reside within the body undetected for months to years. Awakening of the dormant cells starts a cascade resulting in the patient's demise. Despite its established clinical significance, dormancy research and its clinical translation have been hindered by lack of in vitro models that can identify, isolate, and analyze dormancy‐capable cells. We have previously shown that immobilization of cells in a stiff microenvironment induces dormancy in dormancy‐capable cell lines. In this communication, we present a novel biomaterial and an in vitro immobilization method to isolate, analyze, and efficiently recover dormancy‐capable cancer cells. MCF‐7, MDA‐MB‐231, and MDA‐MB‐468 cells were individually coated with agarose using a microfluidic flow‐focusing device. Coated cells were then immobilized in a rigid and porous silica gel. Dormancy induction by this process was validated by decreased Ki‐67 expression, increased p38/ERK activity ratio, and reduced expression of CDK‐2, cyclins D1, and E1. We showed that we can reliably and repeatedly induce dormancy in dormancy‐capable MCF‐7 cells and enhance the dormancy‐capable sub‐population in MDA‐MB‐231 cells. As expected, dormancy‐resistant MDA‐MB‐468 cells did not survive immobilization. The dormant cells could be awakened on demand, by digesting the agarose gel in situ, and efficiently recovered by magnetically separating the silica gel, making the cells available for downstream analysis and testing. The awakened cells were shown to regain motility immediately, proliferating, and migrating normally.